Stimulation of reverse transcriptase generated cDNAs with specific indels by template RNA structure: retrotransposon, dNTP balance, RT-reagent usage - Penno, Christophe (Nucleic Acids Res, 2017)
RNA dependent DNA-polymerases, reverse transcriptases, are key enzymes for retroviruses and retroelements. Their fidelity, including indel generation, is significant for their use as reagents including for deep sequencing. Here, we report that certain RNA template structures and G-rich sequences, ahead of diverse reverse transcriptases can be strong stimulators for slippage at slippage-prone template motif sequence 3′ of such ‘slippage-stimulatory’ structures. Where slippage is stimulated, the resulting products have one or more additional base(s) compared to the corresponding template motif. Such structures also inhibit slippage-mediated base omission which can be more frequent in the absence of a relevant stem–loop. Slippage directionality, base insertion and omission, is sensitive to the relative concentration ratio of dNTPs specified by the RNA template slippage-prone sequence and its 5′ adjacent base. The retrotransposon-derived enzyme TGIRT exhibits more slippage in vitro than the retroviral enzymes tested including that from HIV. Structure-mediated slippage may be exhibited by other polymerases and enrich gene expression. A cassette from Drosophila retrotransposon Dme1_chrX_2630566, a candidate for utilizing slippage for its GagPol synthesis, exhibits strong slippage in vitro. Given the widespread occurrence and importance of retrotransposons, systematic studies to reveal the extent of their functional utilization of RT slippage are merited.